(untitled) (Proceedings of the Society of Antiquaries of Scotland, 2021)
Christian MacLagan (1811-1901), from Stirling, occupies the intersection of amateur antiquarian-ism and modern archaeology. Although not Scotland’s earliest female archaeologist, she pioneered the compilation and publication of prehistoric sites, using her own plans and fieldwork. This paper examines her previously undocumented social background and the roots of her maternal family, the Colvilles, and their fortune in the colonial indigo trade in Bengal. Colville links with Annfield estate, Stirling and Laws, Monifieth, are noted. A large Calcutta-derived legacy in 1859 enabled MacLagan to circumvent many conventional restrictions on women.